Trophic Structure and Isotopic Niche of Invaded Benthic Communities on Tropical Rocky Shores - Larissa M. Pires-Teixeira; Vinicius Neres-Lima; Plínio C. Barbosa; Joel C. Creed (Biology)
When a species is introduced in a new location, it is common for it to establish itself when it finds favorable conditions in the receptor community with regard to interspecific interactions with native species. The azooxanthellate corals Tubastraea coccinea and Tubastraea tagusensis are invasive species introduced in the Caribbean Sea, the Gulf of Mexico, and the Brazilian Southwest Atlantic. They are successful competitors for space, have multiple reproductive modes, and have high larval dispersion and recruitment, but studies on food and trophic relationships of the genus Tubastraea are still scarce. In the present study, we used isotopic values of δ13C and δ15N to investigate trophic relationships in rocky shore communities invaded by T. tagusensis and T. coccinea corals under different oceanographic and anthropogenic contexts. Using metrics derived from the isotopic values, we show that invaded communities have a lower degree of trophic diversity, with species characterized by similar trophic ecologies while abiotic factors seem to contribute to the biotic resistance of communities exposed to invasion events. Tubastraea spp. occupy a niche space similar to that occupied by the native community of suspension feeders, sharing resources already consumed by the receptor community, which makes invading corals successful competitors for food.